Penile squamous cell carcinoma related to high risk HPV infection - Harsono, Erliana Tantri; Siswati, Agnes Sri; Diovani, Sonia; Andayani, Raden Roro Rini; Dyah Ayu Mira Oktarina (Published by Universitas Gadjah Mada, 2025)
Penile cancer is an uncommon form of malignancy, with squamous cell carcinoma (SCC) being the most common subtype. Human papillomavirus (HPV) infection is strongly associated with the development of penile SCC, particularly strains 16 and 18. This report presents two cases of penile SCC related to HPV type 18 infection and discusses the diagnosis and role of HPV in penile cancer. It aims to illustrate the clinical presentation and diagnostic challenges of penile SCC, with emphasis on the role of HPV infection. Case 1 involves a 41 yo man with a verrucous mass on the glans penis, diagnosed as well-differentiated SCC, with HPV type 18 detected. Case 2 is a 54 yo man presenting with multiple ulcerative plaques on the distal glans, also diagnosed as SCC with HPV type 18. Penile SCC can be classified into HPV-associated and non-HPV-associated subtypes. The HPV-associated SCC, more commonly seen in younger patients, is driven by viral oncogenes E6 and E7, which disrupt tumor suppressor proteins. The pathogenesis is similar to that seen in cervical cancer. Diagnosis is confirmed through histopathology and genotyping, while treatment involves surgical excision, with possible radiotherapy and chemotherapy depending on lymph node involvement. Early detection and diagnosis of penile SCC are critical for effective treatment. The HPV infection plays a significant role in the pathogenesis of penile SCC, highlighting the importance of HPV vaccination in prevention. Multidisciplinary management is essential for improving patient outcomes